Challenging spaces: Liminal positions and knowledge relations in dynamic research partnerships - Wallin, Patric; Aarsand, Liselott (International Journal for Students as Partners, 2019)
This article draws upon concepts of liminality and Third Space to explore what happens when undergraduate students become research partners and illustrates how various positions emerge, change, and fluctuate within the educational space of an interdisciplinary course. Based on perspective dialogues with student groups who have worked on research projects concerned with learning environments in higher education, we discuss which experiences from various academic spaces the students make relevant and useas resources in their group work. Furthermore, we highlight how the act of challenging traditional knowledge hierarchies and well-established roles also involves a revision of students’ relations to each other.